2010
DOI: 10.1002/dev.20519
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and emotion regulation: the role of autonomic nervous system reactivity

Abstract: The aim of the present study was to examine the moderating role of parasympathetic and sympathetic nervous system functioning on the relationship between child temperament and emotion regulation. Sixty-two 4.5 year olds (31 females) were rated by their parents on temperamental surgency. Respiratory sinus arrhythmia (RSA) and pre-ejection period (PEP) were measured at baseline and in reaction to an interaction with an unfamiliar person and a cognitive test. The preschoolers’ ability to self-regulate emotion was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 64 publications
2
45
0
Order By: Relevance
“…A recent study used both high-threat and low-threat versions of the TSST in typically developing (TD) children and found that the low-threat version of the TSST was associated with longer PEP than the standard high-threat protocol, indicating reduced SNS engagement during low SET (Yim et al, 2015). In this context, SNS activation is likely adaptive (Quas et al, 2012) and has been associated with improved emotional regulation (Schuengel et al, 2009; Stifler et al, 2011). Thus, ANS measures of arousal in social contexts could serve as an important biomarker for psychiatric disorders associated with social impairments.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study used both high-threat and low-threat versions of the TSST in typically developing (TD) children and found that the low-threat version of the TSST was associated with longer PEP than the standard high-threat protocol, indicating reduced SNS engagement during low SET (Yim et al, 2015). In this context, SNS activation is likely adaptive (Quas et al, 2012) and has been associated with improved emotional regulation (Schuengel et al, 2009; Stifler et al, 2011). Thus, ANS measures of arousal in social contexts could serve as an important biomarker for psychiatric disorders associated with social impairments.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, at least one study found that low-surgent children displayed higher levels of negative emotion in a disappointing situation than high-surgent children (Stifter, Dollar, & Cipriano, 2011). Thus, the ability to regulate negative emotions is likely also very important for low-surgent children's social adjustment (e.g., Coplan et al, 1994; Rubin et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, given low-surgent children's inclination toward negative reactivity and withdrawal, as well as their risk for developing behavioral wariness in social situations (Coplan et al, 1994; Rubin et al, 1995; Stifter et al, 2011), we hypothesized that children low in surgency who used passive emotion regulation strategies (e.g., self-soothing behaviors) instead of active independent strategies (e.g., goal-directed behavior) would show higher levels of behavioral wariness around unfamiliar peers. In other words, because low-surgent children likely need to up-regulate approach behaviors and show more assertive, goal-driven behaviors in the peer context, passive emotion regulation strategies are likely to perpetuate their inclination toward withdrawing from situations that are challenging and uncomfortable.…”
Section: Introductionmentioning
confidence: 99%
“…Observational measures of infant distress in the present study reflect the contribution of both emotional reactivity and regulation, which are inherently intertwined at the behavioral level. Use of physiological measures (e.g., heart rate) would permit better separation of these factors (Stifter, Dollar, & Cipriano, 2011). Furthermore, despite our consideration of many variables that might confound the relation between PTE and infant outcomes, unmeasured covariates may still play a role.…”
Section: Discussionmentioning
confidence: 99%